2019
DOI: 10.1038/s41385-018-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

A screen of Crohn's disease-associated microbial metabolites identifies ascorbate as a novel metabolic inhibitor of activated human T cells

Abstract: Microbial metabolites are an emerging class of mediators influencing CD4+ T cell function. To advance the understanding of direct causal microbial factors contributing to Crohn’s disease, we screened 139 predicted Crohn’s disease-associated microbial metabolites for their bioactivity on human CD4+ T cell functions induced by disease-associated T helper 17 (Th17) polarizing conditions. We observed 15 metabolites with CD4+ T cell bioactivity, 3 previously reported and 12 unprecedented. A deeper investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 70 publications
0
44
0
1
Order By: Relevance
“…Bacterial metabolites mediate many of the protective functions of resident bacteria and are notably abnormal in the dysbiosis associated with IBD (51,52). Metabolites with known immunoprotective activities include the short chain fatty acids (SCFAs), butyrate and propionate, tryptophan metabolites, particularly indoles that serve as AhR ligands, sphingolipids and bile acid derivatives (49,50,(53)(54)(55)(56)(57)(58).…”
Section: Metabolic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial metabolites mediate many of the protective functions of resident bacteria and are notably abnormal in the dysbiosis associated with IBD (51,52). Metabolites with known immunoprotective activities include the short chain fatty acids (SCFAs), butyrate and propionate, tryptophan metabolites, particularly indoles that serve as AhR ligands, sphingolipids and bile acid derivatives (49,50,(53)(54)(55)(56)(57)(58).…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…Metabolites with known immunoprotective activities include the short chain fatty acids (SCFAs), butyrate and propionate, tryptophan metabolites, particularly indoles that serve as AhR ligands, sphingolipids and bile acid derivatives (49,50,(53)(54)(55)(56)(57)(58). However, this is a rapidly developing field with new bacterial metabolites associated with IBD and yet unknown functions being frequently described (51,52,59). We provide several examples of how gnotobiotic mice can help dissect functions of two key immunoprotective bacterial metabolites, SCFA and indoles, since we discussed functional studies of sphingolipids in a previous section.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…Besides taxonomic changes at the level of increased or decreased species relative abundances (Figure 6Cand Table S10), the MGH03D-associated microbiota was functionally characterized by the enrichment and depletion of genes from several metabolic pathways (Figure S5andTable S10). These included functions involved in host-microbe interactions (sialic acids biosynthesis; (Varki and Gagneux, 2012) ) and pathways that were previously associated with IBD, such as for the biosynthesis of biotin(Das et al, 2019) and ascorbate, which has been identified as a microbial metabolite in Crohn's disease patients with inhibitory effects on activated human CD4+ effector T cells(Chang et al, 2019) . Together, these functions are suggestive of a pro-inflammatory microbiota milieu that was transferred from MGH03D via FMT and prevented resolution of rCDI symptoms in some post-FMT patients.In summary, species and strain-level microbiota analysis indicates that failure to treat rCDI by FMT is associated with reduced donor-derived microbiota fractions in patients immediately after treatment; yet FMT from questionable donors can result in the adoption of atypical donor microbiota profiles in post-FMT patients, independently of treatment success, potentially inducing a pro-inflammatory microbiota milieu and failure to resolve rCDI symptoms, at least in some patients.…”
mentioning
confidence: 99%
“…Similarly, ascorbate is considered a bioactive microbial metabolite related to CD and can induce T cell apoptosis by targeting the energy metabolism of activated effector CD4 + T cells. 212 In addition, circulating metabolites such as mevalonate and dimethylglycine, which are produced by a consortium of 11 rare bacteria (predominately Bacteroidetes) isolated from healthy individuals feces, seem to potentiate the systemic development of IFN-γ + CD8+ T cells, thereby combating the intracellular pathogen Listeria monocytogenes (L. monocytogenes) and enhancing ICI-mediated anti-tumor immunity in mice with melanoma. 43,213 This groundbreaking research has demonstrated that rare microbiome members potentially harbor profound effects on host immunity.…”
Section: Additional Microbially Derived Metabolitesmentioning
confidence: 99%